Real-World Patients’ Diagnosis-to-Treatment Journey with Nontuberculous Mycobacterial Pulmonary Disease: A Cross-Sectional Survey - Kozo Morimoto; Jack R. Gallagher; Dirk Wagner; David E. Griffith; Jakko van Ingen (Infectious Diseases and Therapy, 2024)
Abstract Introduction The incidence and prevalence of nontuberculous mycobacterial pulmonary disease (NTM-PD) are increasing globally. Approximately 80% of NTM-PD cases in Japan and five countries within Europe (Eur5; France, Germany, Italy, Spain, and the UK) are caused by Mycobacterium avium complex (MAC). This study describes the clinical decision-making process associated with the management of patients with NTM-PD in Japan and the Eur5. Methods We analyzed data from a survey conducted between July 2013 and October 2013 among physicians treating patients with NTM-PD in clinical practice to compare the healthcare settings, clinical presentation, and patient management in Japan and the Eur5. Results Overall, 619 physicians (Japan, 173; Eur5, 446) participated in the survey. Most patients in Japan (85%) and the Eur5 (79%) were diagnosed with MAC-PD. Patients were managed generally in hospital-based outpatient clinics (117/173, 68%) in Japan and research/teaching hospitals affiliated with medical schools (140/446, 31%) in the Eur5. The most common reason for delaying treatment was the patient’s symptoms not being considered serious enough for treatment (55/128, 43%) in Japan and awaiting results of antimicrobial susceptibility testing (44/151, 29%) in the Eur5. Culture negativity was less commonly achieved after treatment in patients in Japan versus those in the Eur5 (31% [73/238] vs. 70% [300/426], p < 0.0001). In treatment phases that were either completed or discontinued, the primary goal was symptomatic improvement, followed by achieving culture conversion, in both Japan and the Eur5. Overall, 19% (16/85) of physicians in Japan and 43% (220/511) in the Eur5 were “entirely satisfied” with their patients’ treatment outcomes. Conclusions Similarities and differences exist in the healthcare settings, clinical presentation, and management of patients with NTM-PD in Japan and the Eur5. Insufficient consideration of culture status by physicians, delayed treatment initiation, and symptom-based cessation emphasize the need for educational efforts on the guideline-based strategies.